Advanced examination techniques in orthopaedics (GMM, 2003)
This book covers clinical examination in orthopaedics at an advanced level, bringing together important techniques and concepts that can normally only be found in large, specialist surgical texts. It adopts a systemic approach, taking each region in turn, and uses bullet points, key information tables, algorithms, summary boxes and clear photographs or line drawings to present information in an easy-to-read way and to and highlight important hints and common pitfalls